Gestión del marketing de Agroquímicos "Su Economía" en la Parroquia Mata De Cacao del cantón Babahoyo periodo 2023. - Cedeño Vargas, Rissoly Elizabeth (2024)
The present case study was carried out in Agrochemicals Su Economía of the Babahoyo Canton, which aims to analyze the marketing management of Agrochemicals in the period 2023, applying research techniques that allowed us to provide recommendations that help the company in question to position itself strategically. in the market. The use of the descriptive research method with a qualitative and quantitative approach was used to detail the study variable and therefore the respective problem, the collection of information was carried out through techniques such as a survey with the instrument of a structured questionnaire in a format of 8 closed questions and the SWOT matrix with the 9 quadrant design. In the same way, the relevant theoretical bases were considered with the authors' expressions about marketing management, benefits, importance, customer, satisfaction, etc. Since it is essential for companies to establish efficient communication mechanisms to learn more about customers and their preferences, thus obtaining loyalty opportunities. Thus, Agrochemicals Su Economía, given the lack of personalization services and promotion of its products, must take advantage of digital marketing as a strategy and mechanism to learn more about its customers, promoting the products it offers and thus avoiding shortcomings in performance and positioning.